2007
DOI: 10.1002/jctb.1759
|View full text |Cite
|
Sign up to set email alerts
|

Nitrification monitoring in a biofilter treating pig manure

Abstract: BACKGROUND: Nitrogen removal by organic biofilters treating pig manure is incomplete and has to be optimized. This could be achieved by promoting the activity of denitrifiers, this being the limiting factor for nitrogen removal in this kind of process. However, changing the operating conditions could impair nitrification; no data are currently available about the activity and distribution of nitrifiers in organic biofilters. A better knowledge of the process of colonization by nitrifiers is needed to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…When investigating the biofilm thickness in a trickling filter, Persson et al (2002) effectively found that it decreases with depth. Moreover, potential nitrifying and denitrifying activities measured ex-situ were much greater than activities observed inside the trickling biofilters, suggesting the possibility to enhance nitrogen removal (Gilbert et al, 2007(Gilbert et al, , 2008. Moreover, potential nitrifying and denitrifying activities measured ex-situ were much greater than activities observed inside the trickling biofilters, suggesting the possibility to enhance nitrogen removal (Gilbert et al, 2007(Gilbert et al, , 2008.…”
Section: Nitrogen Behavior Inside Biofiltermentioning
confidence: 88%
“…When investigating the biofilm thickness in a trickling filter, Persson et al (2002) effectively found that it decreases with depth. Moreover, potential nitrifying and denitrifying activities measured ex-situ were much greater than activities observed inside the trickling biofilters, suggesting the possibility to enhance nitrogen removal (Gilbert et al, 2007(Gilbert et al, , 2008. Moreover, potential nitrifying and denitrifying activities measured ex-situ were much greater than activities observed inside the trickling biofilters, suggesting the possibility to enhance nitrogen removal (Gilbert et al, 2007(Gilbert et al, , 2008.…”
Section: Nitrogen Behavior Inside Biofiltermentioning
confidence: 88%